2019
DOI: 10.48550/arxiv.1909.07520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Unsupervised Segmentation of Extreme Weather Events

Adam Rupe,
Karthik Kashinath,
Nalini Kumar
et al.

Abstract: Extreme weather is one of the main mechanisms through which climate change will directly impact human society. Coping with such change as a global community requires markedly improved understanding of how global warming drives extreme weather events. While alternative climate scenarios can be simulated using sophisticated models, identifying extreme weather events in these simulations requires automation due to the vast amounts of complex high-dimensional data produced. Atmospheric dynamics, and hydrodynamic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Machine learning (ML) and deep learning (DL) methods were shown to be useful tools in problems of pattern recognition, visual object detection and other computer vision tasks [42][43][44][45][46]. In recent studies, successful application of ML methods was shown when identifying extreme weather events in reanalyses data [47][48][49]. Most research groups focus on the identification of synoptic-scale atmospheric phenomena, such as tropical cyclones [50,51] and atmospheric rivers [52], because of clear representation of these events in most observational data and simulated atmospheric dynamics data.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) and deep learning (DL) methods were shown to be useful tools in problems of pattern recognition, visual object detection and other computer vision tasks [42][43][44][45][46]. In recent studies, successful application of ML methods was shown when identifying extreme weather events in reanalyses data [47][48][49]. Most research groups focus on the identification of synoptic-scale atmospheric phenomena, such as tropical cyclones [50,51] and atmospheric rivers [52], because of clear representation of these events in most observational data and simulated atmospheric dynamics data.…”
Section: Introductionmentioning
confidence: 99%